2016
DOI: 10.1186/s12903-016-0210-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant PDGF-BB on bone formation in the presence of β-tricalcium phosphate and bovine bone mineral matrix: a pilot study in rat calvarial defects

Abstract: BackgroundSupplementation of bone substitutes with recombinant platelet-derived growth factor-BB (PDGF-BB) can enhance bone regeneration. The aim of the study was to evaluate the effect of PDGF-BB on bone formation in the presence of β-tricalcium phosphate and bovine bone mineral matrix in a rat calvaria defect model.MethodsThe authors examined 5 mm rat calvarial defects treated with β-tricalcium phosphate (TCP) or demineralized bovine bone mineral (DBBM) with and without 0.3 mg/ml recombinant PDGF-BB. Calvari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The MPM kit consisted of four 9-mL tubes without anticoagulant, one 9-mL preparation tube, two sterile containers, 0.5 cc β-TCP bone graft, and a 6-mL injection syringe. Growth factors are susceptible to β-TCP granules and show satisfactory effects on tissue regeneration [54,55]. Xenogeneic bone graft materials resorb slowly and growth factors are not affinitive to xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…The MPM kit consisted of four 9-mL tubes without anticoagulant, one 9-mL preparation tube, two sterile containers, 0.5 cc β-TCP bone graft, and a 6-mL injection syringe. Growth factors are susceptible to β-TCP granules and show satisfactory effects on tissue regeneration [54,55]. Xenogeneic bone graft materials resorb slowly and growth factors are not affinitive to xenografts.…”
Section: Discussionmentioning
confidence: 99%
“… Xie et al (2014) found that the secreted PDGF-BB from preosteoclasts increased type H vessel numbers and bone formation during bone modeling remodeling. In contrast to the mentioned studies, Luvizuto et al (2016) reported that the supplementation of biomaterials with PDGF-BB had no remarkable effects on bone formation. Despite the beneficial effects, PDGF-BB has a short half-life within the blood; thus, local and sustained delivery of PDGF-BB is essential to achieve ideal outcomes.…”
Section: Importance Of Angiogenesis In Bone Development and Repairmentioning
confidence: 69%
“…Moreover, collagen membranes releasing PDGF enhanced the regeneration of mandibular defects compared to conventional collagen membranes (Yamano, Haku, Yamanaka, Dai & Takayama, ). On the contrary, adding PDGF‐BB to TCP and DBBM did not impact on the regeneration of calvarial CSDs in rats (Luvizuto, Tangl, Dobsak, Reich & Gruber, ; Silva de Oliveira, Okamoto, Sonoda, Poi & Garcia Junior, ).…”
Section: Resultsmentioning
confidence: 99%